Leptin Modulates the Expression of miRNAs-Targeting POMC mRNA by the JAK2-STAT3 and PI3K-Akt Pathways - Derghal, Adel (J Clin Med, 2019)
The central control of energy balance involves a strongly regulated neuronal network within the hypothalamus and the brainstem. In these structures, pro-opiomelanocortin (POMC) neurons are known to decrease food intake and to increase energy expenditure. Thus, leptin, a peripheral signal that relays information regarding body fat content, modulates the activity of POMC neurons. MicroRNAs (miRNAs) are short non-coding RNAs of 22–26 nucleotides that post-transcriptionally interfere with target gene expression by binding to their mRNAs. It has been demonstrated that leptin is able to modulate the expression of miRNAs (miR-383, miR-384-3p, and miR-488) that potentially target POMC mRNA. However, no study has identified the transduction pathways involved in this effect of leptin on miRNA expression. In addition, miRNAs targeting POMC mRNAs are not clearly identified. In this work, using in vitro models, we have identified and confirmed that miR-383, miR-384-3p, and miR-488 physically binds to the 3′ untranslated (3′UTR) regions of POMC mRNA. Importantly, we show that leptin inhibits these miRNAs expression by different transduction pathways. Taken together, these results allowed us to highlight the miRNA involvement in the regulation of POMC expression downstream of the leptin signaling and satiety signal integration.